1979
DOI: 10.1071/zo9790699
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic Studies on Cyclorana and Associated Genera of Australian Frogs.

Abstract: The taxonomic relationships of frogs from the genus Cyclorana are uncertain, for they share similarities with both the Leptodactylidae and the Hylidae. Karyotypic comparisons were made between seven species of Cyclorana and three species from the leptodactylid genera Notaden, Neobatrachus and Heleioporus. All Cyclorana species have 2n = 26, whereas the other species have 2n = 24. The position and type of secondary constrictions subdivide the species of Cyclorana into three groups. The similarity of chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In agreement with earlier investigations (Morescalchi and Ingram, 1974;King et al, 1979;Mahony and Robinson, 1986), both species have a diploid chromosome number of 2n = 24. All chromosomes are biarmed and can be arranged in 12 pairs (Fig.…”
Section: Constitutive Heterochromatin and Nucleolus Organizer Regionssupporting
confidence: 79%
See 1 more Smart Citation
“…In agreement with earlier investigations (Morescalchi and Ingram, 1974;King et al, 1979;Mahony and Robinson, 1986), both species have a diploid chromosome number of 2n = 24. All chromosomes are biarmed and can be arranged in 12 pairs (Fig.…”
Section: Constitutive Heterochromatin and Nucleolus Organizer Regionssupporting
confidence: 79%
“…A small number of studies on the chromosomes of the genus Mixophyes have been performed using conventional staining and silver labeling of the nucleolus organizer regions (Morescalchi and Ingram, 1974;King et al, 1979;Mahony and Robinson, 1986). All four species possess 2n = 24 very similar biarmed chromosomes and one pair of nucleolus organizers.…”
Section: Copyright © 2002 S Karger Ag Baselmentioning
confidence: 99%
“…Although only one species, L infrafrenata, has been karyotyped for New Guinean pelodriadine hylids, the karyotypes of about two dozen Australian species (Litoria and Cyclorana) are available for comparison (King, 1980;King et al, 1979;Morescalchi and Ingram, 1974;Stephenson and Stephenson, 1970;. The Australian and New Guinean species of the genus Litoria have the following karyotypic features in common.…”
Section: Discussionmentioning
confidence: 99%
“…Menzies and Tippett (1976), examining 22 Litoria and six Nyctimystes species of Papua New Guinea, reported that the chromosome number of Papuan hylids (including L. angiana) is 2n=26, with the exception of L. infrafrenata with 2n =24 chromosomes. Karyological studies on the Australian species including the genus Cyclorana (King, 1980;King et al, 1979;Morescalchi, 1979;Morescalchi and Ingram, 1974;Stephenson and Stephenson, 1970) confirmed that the basic diploid number of the pelodryadine frogs is 26.…”
mentioning
confidence: 88%